An International Collection of Multidisciplinary Approaches to Violence and Aggression - Lewis, Catherine (IntechOpen, 2023)
This book is a collection of theoretical perspectives and research studies from international scholars on neuropsychological aspects of aggression, personality features, gender-based violence, and cultural origins of conflict. Written by experts in the field, it offers insights into multi-theoretical perspectives on aggression and violence and the multifaceted factors involved in the etiology and management of conflict. This useful resource presents perspectives from Western and non-Western frameworks of violence, broadening the spectrum of the shared knowledge base.